2010
DOI: 10.1177/0022034510385243
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the MTHFR C677T Polymorphism and Alcohol—Impact on Oral Cancer Risk and Multiple DNA Methylation of Tumor-related Genes

Abstract: Several studies have reported Oral Squamous Cell Carcinoma (OSCC) association with etiological factors, such as smoking and alcohol. The aim of the present study was to establish whether the methylenetetrahydrofolate reductase (MTHFR) C677T genotype and a high alcohol intake, solely or in interaction, have an impact on the oral cancer risk, DNA methylation, or multiple methylation of tumor-related genes. MTHFR C677T genetic polymorphism was determined by the PCR/RFLP method, and DNA methylation was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 28 publications
(42 reference statements)
1
41
0
1
Order By: Relevance
“…To date, interactions between polymorphisms of many susceptibility genes and exposure of environmental carcinogens have been reported to affect the risk for OSCC (Chung et al 2011;Supic et al 2011;Bharti et al 2013). Epidemiologic investigations have shown that tobacco smoking and betel nut chewing are 2 of the major risk factors for OSCC development (Awang 1988;Scully and Bagan 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To date, interactions between polymorphisms of many susceptibility genes and exposure of environmental carcinogens have been reported to affect the risk for OSCC (Chung et al 2011;Supic et al 2011;Bharti et al 2013). Epidemiologic investigations have shown that tobacco smoking and betel nut chewing are 2 of the major risk factors for OSCC development (Awang 1988;Scully and Bagan 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Axume et al (2007) suggested that the MTHFR 677TT genotype and folate interact to lower global leukocyte DNA methylation patterns in young Mexican American women. Meanwhile, Supic et al (2011) resulted in a significant association was found between TT genotype and methylation status of the RASSF1A gene in Oral Squamous Cell Carcinoma (OSCC) patients (P = 0.012). While A polymorphism which changes an A to C at position 1298 (a1298c) in MTHFR is a reasonably common variant of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation in cancer cells is now believed to be one of the major causes of the transcriptional silencing of tumor suppressor genes in carcinogenesis. Accumulating evidence demonstrates aberrant DNA methylation in most human cancers, including colon, breast, lung, and oral carcinomas (Esteller 2007;Belinsky et al 2002;Supic et al 2009Supic et al , 2011a. A number of recent studies have demonstrated that dietary phytochemicals could have an important role in cancer chemoprevention by affecting DNA methylation (Shukla et al 2014).…”
Section: Dna Methylationmentioning
confidence: 99%